Social comparison and risk taking behavior - Astrid Gamba; Elena Manzoni (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
We study theoretically and experimentally decision making under uncertainty in a social environment. We introduce an interdependent preferences model that assumes that the decision maker evaluates monetary outcomes in relation both with his individual and his social reference point. In the experiment we reproduce a workplace environment whereby subjects interact in an effort task, earn (possibly) different wages from this task and then undertake a risky decision that may give them an extra bonus. Controlling for intrinsic risk attitudes, we find that both downward and upward social comparison strongly influence risk attitudes and that they both generate more risk loving behavior. Moreover, we find that a propension to envy counterposes such effect, by increasing risk aversion.
Keywords: C91; D03; D81; 330; interdependent preferences; reference point; risk aversion; Social comparison